Supplementary Learning Resource Package in Science 10 Physics - Decoriña, Dante M. (Future Science / FSH-PH Publications, 2022)
Physics is a difficult subject for the vast majority of Filipino students to learn. It is also a challenge for educators worldwide to create learning media that makes it easier to explain the material especially in learning fields that require a reasonably high level of understanding, such as Physics. The use of high-quality instructional materials facilitates and improves the teaching and learning process. This study aimed to develop and evaluate a supplementary learning resource package in Physics for Grade 10 Science. Descriptive method of research was used in this research. The respondents of the study were the thirty science teachers and fifteen science experts who evaluated the materials based on the set standards. The study showed that the supplementary learning resource package is acceptable for use by teachers and students for independent learning particularly in the new normal education. It is recommended that the supplementary learning resource package be further validated in order to provide more effective instructional materials to both learners and teachers, and that other science teachers be encouraged by their school heads to develop similar learning packages.